PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KINERJA PERUSAHAAN PADA SEKTOR KEUANGAN YANG TERCATAT DI BURSA EFEK INDONESIA PADA TAHUN 2007-2010 - Hastuti, Rini Tri; Suhendah, Rousilita (Jurnal Ekonomi, 2015)
This research examine the effect of insider ownership and institutional ownership on corporate performance on  financial sector that listed in Indonesia Stock Exchange on 2007-2010.There is 11th  banking on this sample with multiple purposive sampling criteria. Research data was collected from Indonesian Capital Market Diectory. This research findings are insider ownership  significant effected  operational expenses to operational income  ratio and Loan to deposit ratio. But this failed to examine that institusional ownership  effect operational expenses to operational income  ratio and Loan to deposit ratio.  The result of this study revealed that  insider ownership and institusional ownership did not affect leverage.